**t**an(**t**) + sec(**t**) = 1 sin(**t**)/cos(**t**) + 1/cos(**t**) = 1 [sin(**t**) + 1]/cos(**t**) = 1 sin(**t**) + 1 = cos(**t**) # ...(**t**) + 2 sin(**t**) + 1 = 1 - sin²(**t**) 2 sin²(**t**) + 2 sin(**t**) = 0 2 sin(**t**) [sin(**t**) + 1] = 0 sin(**t**) = 0,**t**= 0 + π...2 Answers · Science & Mathematics · 30/11/2009

1 / (

**t**+ 5) = (-4 + 1) / (**t**+ 2) Ok, this problem is a little long. First... fix that by multiplying each side by 1 in the forms of... (**t**+ 2) / [(**t**+ 5)(**t**+ 2)] = [-3(**t**+ 5)] / [(**t**+ 2)(**t**+ 5)] now we set a side equal to...1 Answers · Education & Reference · 09/04/2009

v(

**t**) = sin²(√(**t**)) rearranging**t**o show work... v(**t**) = [sin√(**t**)]² chain rule: mul**t**iply**t**he power ou**t**fron**t**... cos, bu**t****t**he deriva**t**ive of**t**he &quo**t**;s**t**uff&quo**t**; (√(**t**) or**t**^(½) ) is ½**t**...2 Answers · Science & Mathematics · 24/03/2010

**t**- 5(**t**- 1) = 4t + 12**t**- 5t + 5 = 4t + 12 -4t + 5 = 4t + 12 5 = 8t +12 -7 = 8t**t**= -7/83 Answers · Education & Reference · 24/06/2009

**t**mobile because it gives you the my faves plans. i used to have a regular plan with 700 mins and i couldn'**t**talk except at night in fear of running my mins. i would always come...11 Answers · Consumer Electronics · 13/03/2008

y = (a

**t**^2)/2 Subtract (a**t**^2)/2 from both sides: y-(a**t**^2)/2 = 0 Subtract y from both sides: -(a**t**^2)/2 = -y Divide...1 Answers · Science & Mathematics · 02/09/2010

ƒ(

**t**) = 4000(2)^(**t**/3) I**t**'s already &quo**t**;solved&quo**t**; for ƒ(**t**). Jus**t**assign a value**t**o**t**and plug in**t**o calcula**t**or. If you wan**t****t**o solve...1 Answers · Science & Mathematics · 16/05/2010

yep, messy, and didn'

**t**have a chance to answer before: 3sqrt(2t - 3) = 11 - 2sqrt(7 -**t**) square both sides: 9(2t - 3) = 121 - 44sqrt(7 -**t**) + 4(7 -**t**) 18t - 27 = 121 - 44sqrt(7 -**t**) + 28 - 4t 22t - 176 = -44sqrt(7 -**t**) divide everthing by 22:**t**- 8 = -2sqrt(7 -**t**) square...2 Answers · Science & Mathematics · 13/01/2013

f(

**t**) = sum of odd function g(**t**) =**t**, which has a sine series, + G(**t**) =**t**^2, an even function...and left-hand derivatives at 0 and pi, so that since g'(**t**) = 1/2 G'(**t**) we can calculate the Fourier series of...1 Answers · Science & Mathematics · 22/05/2012

Before s

**t**ar**t**ing: sec(**t**) = 1/cos(**t**)**t**an(**t**) = sin(**t**) / cos(**t**)**t**an(**t**) + sec(**t**) = 1.5 [sin(**t**) / cos(**t**...know**t**ha**t**: cos²(**t**) + sin²(**t**) = 1 cos²(**t**) + { [(3/2).cos(**t**)] - 1 }² = 1 cos²(**t**) + (9/4).cos²(**t**) - 3.cos(**t**) + 1 = 1...2 Answers · Science & Mathematics · 15/03/2012

##### Ad

related to: t